Modeling field-scale effects of conservation agriculture practices on soil water balance in the dryland regions of the Yellow River Basin, China - Nangia, Vinay; Du, Jian Tao; Ahmad, Mobin-ud-Din; Yan, Changrong (2007)
Soil erosion by water is a severe problem for sustainability of agricultural systems in the dryland regions of the Yellow River Basin. Conservation agriculture (featuring reduced or zero tillage, mulch retention, crop rotations and cover crops) offers a possible solution. Conservation agriculture systems typically result in increased crop water availability, agro-ecosystem productivity and reduced soil erosion. To evaluate the potential of conservation agriculture to improve soil water balance and agricultural productivity, the DSSAT crop model was calibrated using the data of field experiment in Shou Yang County in the semi-arid northeastern part of the ellow River Basin. Its average annual precipitation is 472mm -75% of which falls during the rowing season. The site had a maize-fallow-maize rotation. We used two crop seasons-2005 and 2006 data from four treatments for calibration and analyses. The treatments were: conventional tillage (CT), no-till with straw mulching (NTSM), all-straw with return till (ASRT) and 1/3rd residue left with rolling till (RRT). The calibration results gave satisfactory agreement between field observed and model predicted values for crop yield and soil moisture contents for the 150cm soil profile for all treatments with difference between observed and predicted values being in the range of 3-25% for maize yield and RMSE in the range of 0.14-0.19cm3/cm3 for observed average soil moisture content. The predicted water productivity for the four treatments during dry year (precipitation 39% less than normal) was 1.59, 1.78, 1.67 and 1.52 kg/m3. and 1.70, 1.71, 1.71 and 1.70kg/m3 during the normal precipitation year (424.8 mm) for CT, NTSM, ASRT and RRT treatments, respectively. During the dry year, CT treatment produced highest ET (226mm) but NTSM treatment produced the highest crop yield (5736kg/ha)-suggesting that evaporative losses from CT treatment were higher than other NTSM treatment. During normal precipitation year, however, CT treatment produced highest ET (326mm) along with highest crop yield (6335kg/ha). During dry year, predicted moisture storage (_S) in the 150cm soil profile increased by 60% more for NTSM treatment compared to CT treatment. During normal precipitation fallow period, NTSM treatment predicted _S decreased by 63% less than CT treatment. These preliminary results are based on a two-year dataset and further long term analyses need to be carried out for improving the understanding of the conservation agriculture cropping systems in the Yellow River Basin.